APLIKASI NPV AT RISK DALAM ANALISIS KELAYAKAN FINANSIAL BUDIDAYA JAMUR TIRAM PUTIH DI KABUPATEN BOGOR JAWA BARAT - Tintin Sarianti; Hendro Sasongko; Anny Ratnawati (Jurnal Manajemen & Agribisnis, 2008)
The purpose of this study where to analyze white oyster mushroom farming activity in Sub-Province of Bogor, to analyze financial feasibility of  white oyster mushroom farming activity for high and low land in Sub-Province of Bogor by NPV at Risk Method and to analyze the switching value for the changes of cost and benefit in  white oyster mushroom farming activity.  The data were collected from 6 farmer living in high and low land in Sub-Province of Bogor. The NPV at risk model and switching value analysis were used to analyze tha data.  The result of the study showed that white oyster mushroom farming activity for high and low land in Sub-Province of Bogor were feasible by financial that considered by investors in selecting the location to act the white oyster mushroom farming.  The risks like price risk, production risk in that activity have accomodated in to cash flow.  Accomodation for price risk was used the inflation rate and for production risk was used estimation for failure of crop in white oyster mushroom farming activity according the farmers in location.  Switching value was used for to analyze maximum changes in cost and benefit which were developing the cash flow.  The maximum changes describes that the changes admit of tolerated.  The result for switching value analysis showed that the decreasing of production of white oyster mushroom (fresh and baglog) more sensitive than the others (decreasing of fresh white oyster mushroom price and increasing of varible input cost).  This matter showed that production risk having an effect on white oyster mushroom farming activity than price risk.  According that situation, the farmer must be repaire the technology of  white oyster mushroom farming activity. The application of this model gives many outputs (NPV) and risks variabilities so that it can give  a much more attractive and variying recommendation especially for the investors to do the investment decision especiaaly for white oyster mushroom farming activity